The Mind of Kierkegaard - Collins, James, 1917-1985 (Book collections on Project MUSE., 1983)
This introductory overview of Kierkegaard's writings summarizes their central arguments and places them in their historical context. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.